Assessment of Carbon Dioxide Emission and Its Impact on High-Rise Mixed-Use Buildings in Egypt - Hamza, Ahmed Salah (AUC Knowledge Fountain, 2021)
With Egypt's vision of 2030 focusing on sustainable development with a true emphasis on Carbon Dioxide (CO2) emission reduction in the newly built cities and high-rise buildings, efforts are exerted on various levels towards accomplishing the vision’s goals. This is achieved through multiple tools and models associated with aiding the reduction of carbon emissions, yet not a clear one was introduced for the mixed-use buildings in Egypt. Through this work, a significant gap was identified with respect to high-rise buildings carbon emission assessment in Egypt. This was a main driving force for this work in an attempt to develop a computational model that can be useful in this regard. The investigation is undertaken with a goal to pinpoint existing sustainability methods used in the development and design of the world's high-rise mixed-use infrastructures. In addition, this work attempts to identify adequate approaches that can contribute to a more effective, environmentally safe, and space-efficient construction of mixed-use high-rise building in Egypt. This aims ultimately at defining the driving factors of carbon dioxide emissions relevant to the building phase and recommend strategies to encourage more environmentally sustainable approaches where appropriate. This study develops and evaluates a comprehensive carbon model framework for high-rise building construction and operation activities and testing the model’s validation through analytic analysis. The outcome of this study should contribute to a much-needed roadmap to reduce Carbon Dioxide (CO2) footprints in Egypt and possibly lay the groundwork to replicate the study in other building sectors and regions. This would also develop sensitivity analytics to envision carbon emissions of buildings within the construction phase and operational phase using various sustainable construction materials and mixes-primarily for concrete, bricks, and steel, and in the operational phase using alternative sustainable products primarily for lighting, air conditioning systems, water heaters, and window glazing. Similar to other work, future work should be resumed to further develop, enhance and adapt this model in order to suit the nature of projects, service conditions together with other parameters. Keywords: (Carbon Dioxide, Mixed-Use high-rise buildings, Construction phase, Concrete, Bricks, Operational Phase)